The concept and the essence of academic mobility of students - Moly Francesco, L.; Murtaza, A.; Chukubayev, Y. (Farabi Journal of Social Sciences, 2020)
The article discusses the theoretical foundations of academic mobility of students. The concept of determining the academic mobility of students is clarified. The author characterizes the types of academic mobility of students, reveals the features of their organization in universities. The subjects of academic mobility of students and certain requirements for them are identified. The analysis of the tasks of organizing academic mobility of students facing Russian universities, as well as different types of activities for teaching students under the program of academic mobility, are presented. In legal acts and statutes of universities (MSU. Academic mobility is considered as the movement of someone related to education for a certain (usually up to a year) period to another educational institution (in their home country or abroad) for training, teaching or research, after which the student, teacher or researcher returns to their primary educational institution. This concept is not associated with emigration or a long period of study (work) abroad.